Double-balloon catheter and sequential vaginal prostaglandin E2 versus vaginal prostaglandin E2 alone for induction of labor after previous cesarean section - Kehl, Sven; Weiß, Christel; Sütterlin, Marc (Archives of gynecology and obstetrics, 2016)
Purpose: To evaluate the efficacy of inducing labor using a double-balloon catheter and vaginal prostaglandin E2 (PGE2) sequentially, in comparison with vaginal PGE2 alone after previous cesarean section. Methods: A total of 264 pregnant women with previous cesarean section undergoing labor induction at term were included in this prospective multicentre cohort study. Induction of labor was performed either by vaginal PGE2 gel or double-balloon catheter followed by vaginal PGE2. The primary outcome measure was the cesarean section rate. Results: The cesarean section rate was 37 % without any statistically significant difference between the two groups (PGE2: n = 41, 37 % vs. balloon catheter/PGE2: n = 41, 42 %; P = 0.438). The median (range) number of applications of PGE2 [2 (1-10) versus 1 (0-8), P < 0.001] and the total amount of PGE2 used in median (range) mg [2 (1-15) vs. 1 (0-14), P = 0.001] was less in the balloon catheter/PGE2 group. Factors significantly increasing risk for cesarean section were “no previous vaginal delivery” (OR 5.391; CI 2.671-10.882) and “no oxytocin augmentation during childbirth” (OR 2.119; CI 1.215-3.695). Conclusions: The sequential application of double-balloon catheter and vaginal PGE2 is as effective as the sole use of vaginal PGE2 with less applications and total amount of PGE2.
Gesehen am 08.04.2019
Published online: 5 October 2015